(3x-7y)-(x+2y)=

Simple and best practice solution for (3x-7y)-(x+2y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-7y)-(x+2y)= equation:


Simplifying
(3x + -7y) + -1(x + 2y) = 0

Remove parenthesis around (3x + -7y)
3x + -7y + -1(x + 2y) = 0
3x + -7y + (x * -1 + 2y * -1) = 0
3x + -7y + (-1x + -2y) = 0

Reorder the terms:
3x + -1x + -7y + -2y = 0

Combine like terms: 3x + -1x = 2x
2x + -7y + -2y = 0

Combine like terms: -7y + -2y = -9y
2x + -9y = 0

Solving
2x + -9y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9y' to each side of the equation.
2x + -9y + 9y = 0 + 9y

Combine like terms: -9y + 9y = 0
2x + 0 = 0 + 9y
2x = 0 + 9y
Remove the zero:
2x = 9y

Divide each side by '2'.
x = 4.5y

Simplifying
x = 4.5y

See similar equations:

| x^2+3=2 | | ln(x-5)+ln(x)=0 | | 3(2x+4)=2+6+10 | | 5(1-5)+15-6+24+20= | | (6x^2y^-3z^4/3x^5y^-3z^1)^2 | | 10=35x | | 6/11*4/7 | | 3(x-4)(x-4)= | | 5(2X-8)+6=4x-32 | | 4/3m= | | -16+5(-4)-9=x | | e^3x+2=40 | | -sx=-15 | | 18(5c-1)-2=88c+18 | | 22=A+4B-4C | | (12-3+25)6+20-(10+10)= | | (-7-1x)(5-1x)=0 | | 1-3x=22 | | 8=z/4=23 | | -36=-2A-9B+C | | -11-18-4w/5 | | 7(7+25)+(5+6)10= | | 2x-1+5+x=180 | | 8-1/7u5 | | 20+2y-5=9y-13-3y | | 26=4A+2B | | 3(4+25)-12+-15= | | -6x+20=4x-30 | | 18x+12y=165 | | (2a^-5b^4c^3)^-2/(3a^3b^-7c^3)^2 | | A^2-3a-45=0 | | A^2-3a-34=0 |

Equations solver categories